Chronic Illness, Religiosity, and Spirituality in Brazil: Health Professionals’ Perceptions and Guidelines - Borges, Lilian Maria (International journal of Latin American religions, 2022)
Experiencing a chronic illness can arouse feelings of helplessness and fear in the face of the progression and incurability of the disease. In seeking to find meaning or support in this experience, many people tend to develop or refine their spirituality. However, we still need to better understand how diseases and their chronicity impact the religious and spiritual beliefs and attitudes of people who are diagnosed with a condition that requires protracted treatment. This article proposes to explore this idea from a review of the literature and an analysis of the reports of 26 healthcare professionals (doctors, nurses, psychologists, and social workers) working in a hospital in Rio de Janeiro, Brazil. Also, the objective is to recommend some guidelines to help professionals deal with the topic. According to reports obtained in semi-structured interviews, religiosity and/or spirituality can have a positive effect on the patient’s life. They can be sources of comfort and hope, showing potential to alleviate suffering from illness, increasing adherence to their treatments, improving the relationship with the health team, and making the patient more resilient to the adversities arising from this situation. Depending on the way patients articulate their religiosity, they may also have negative effects, such as treatment dropout—in the expectation of a divine cure—or practices contrary to hospital asepsis. Understanding these issues helps to establish professional guidelines aimed at making religiosity or spirituality a positive element in the therapeutic process of patients with different forms of chronic illnesses.